Profesionalisme Room Attendant dalam Menjaga Kebersihan Kamar Tamu pada Hotel Berbintang di Surakarta (Jurnal Manajemen Pariwisata dan Perhotelan, 2025)
Guest comfort is a key indicator of hotel service quality, strongly influenced by the professionalism of Room Attendants and the cleanliness of guest rooms. This study aims to analyze the role of Room Attendant professionalism in maintaining room cleanliness standards at Hotel Grand Mercure Solo Baru. Using a qualitative approach, in-depth interviews with three housekeeping staff members were conducted. The findings show that Room Attendant professionalism contributes directly to room cleanliness and positively impacts guest comfort. Professional attitude, discipline, and responsibility are crucial in ensuring room quality. Additionally, the study highlights the importance of attention to detail, commitment to cleanliness standards, and proactive approaches to maintaining guest rooms. The research also found that regular training and management support are vital for improving Room Attendant professionalism. Encouraging staff to take ownership and motivating them to uphold cleanliness standards is essential. Effective communication between staff and management helps identify and address challenges in room cleanliness practices. The study emphasizes that a motivated and well-trained team contributes significantly to guest satisfaction and loyalty, which in turn supports the hotel's reputation and encourages repeat business. The study suggests that investing in the professional development of Room Attendants is crucial for long-term success in the hospitality industry. It also recommends ongoing performance evaluations, regular feedback, and motivational initiatives to continuously improve service quality. These measures are essential for enhancing guest satisfaction, improving employee morale, and maintaining a competitive edge in the hospitality sector, ultimately contributing to sustainable growth, success, and better overall guest experiences for the hotel.